EFEKTIVITAS PENYERAPAN ANGGARAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MADIUN TAHUN 2020 - Adi Purwanto; Agustin .; Suwardi . (Master of Public Administration, Universitas Slamet Riyadi, 2022)
Budget absorption is one of the indicators that can show the success ofprograms or policies carried out by the government. The realization to budgetratio reflects the absorption of the budget in carrying out various programs thathave been set. With this consideration, the ability to absorb the budget by thelocal government can be an indicator of the performance of the city / districtgovernment.The results showed that the dominant causes of low budgetabsorption in the Office of Public Works and Spatial Planning of Madiun districtin the fourth quarter of 2020 were the Planning factor with a percentage of 4,98%the Implementation of the Budget with a percentage of 3,69%, Human Resourceswith a presentation of 3,75% and procurement of services with a percentage of3,66% % while the main factor in planning led to low budget absorption in thefourth quarter of 2020 was the presence of Government policy on budgetreduction (recofusing) 4,35% Incorrect account determination so that it needsrevision of the document 3,7%, Preparation of budget ceiling is too low not inaccordance with market prices) 3,6%, There is a price adjustment due togovernment policy (escalation) 3,7%, Less effective cash budget planning causesthe implementation of activities / projects not in accordance with the withdrawalplan per quarter / cash budget listed in the DPA form.3,75%Keywords: Effectiveness, Absorption Stack, Martani and lubis